PENERAPAN RCM PADA KOMPRESOR DALAM SISTEM KRIOGENIK - Afdal, Afdal; Sunaryo, Sunaryo; Japri, Japri; Hakim, Legisnal (Jurnal Teknik Industri Terintegrasi (JUTIN), 2020)
In applying maintenance management to the cryogenic system for the production of Oxygen and Nitrogen, you must first know the equipment in the cryogenic system, know the level of damage to the equipment, know how to perform maintenance, know how to prevent and know how to repair. The research objectives to be achieved are: Knowing critical equipment in the cryogenic system in the process of producing Oxygen (O2) and Nitrogen (N2), Determine policy, maintenance maintenance activities based on the distribution of damage, namely the weibull distribution using the Reliabilty Centered maintenance method. on the compressor equipment in the cryogenic system so that no failure occurs, Determine the inspection time interval on the compressor in the Oxygen Plant PT. Indah Kiat Pulp & Perawang Paper. At this stage every failure mode is known. Task selection is carried out to determine the type of maintenance policy that is the most effective for each failure mode. As well as determining the relationship of existing task failures, whether the failure is directly related to Time Directed (TD), Condition Directed (CD), Failure Finding (FF) and grouping of failure modes in the Hidden Failure (D) category. So in the end we get an effective type of treatment. The results of the selection of appropriate treatment measures for the company is with TD (Time Directed) treatment. In calculations using the distribution of damage (Weibull) and identify the value betha (Î²) has a decreased damage rate Î²> 1, amounting to 1.531880662, from the value it is known that the recommended maintenance is Preventive Maintenance and Time Based Maintenance